Leksemy "dobro", "dobry", "dobrze" w listach do redakcji "Monitora" = Lexemes "a good" (noun), "good" (adjective) and "well" (adverbe) in letters to the editorial office of "Monitor" - Gorzelana, Joanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The author presents the results of the analysis of letters to the editor published in the "Monitor" magazine in the years 1765?1769. The aim is to analyse the contexts of the occurrence of the lexeme "good" (noun) and related (adjective, adverb). Particular attention was paid to the determination of people, among whom there are references to the class society (a well?born man) and profession (e.g. a good teacher). Due to the axiological references of the studied lexemes, a partial image of the value system of people of the Enlightenment era emerges from the analysis.
Keywords: oświecenie; "Monitor" - czasopismo; list do redakcji; wartości; dobro; Enlightenment; "Monitor" magazine; letter to the editor; values; good